Studi Kasus Analisis Kegagalan Material Piston Sepeda Motor - Munaji Munaji; Yoyok Winardi (Universitas Muhammadiyah Sidoarjo, 2017)
This paper presents the failure anaylisis on the motorcycle’s piston.The analysis procedure consists of physical observation (metallography), mechanical testing (hardness testing, and chemical composition testing (spectrometry). Result physcal observation shows there are scratches and changes in color on the surface of the piston wall. Based on spectrometer test, piston is made from Al-Si-Cu-Mg alloy with AA336.0 series. Hardness vickers testing showed the distribution ofHVN on the walls and heads of pistonare not decrease significantly. Hardness on the head of piston is 136.06 HVN, while on the wall of piston is 134.3 HVN. Based on the analysis, the failure is caused by lubrication failure that causes piston over heat and burning.